2013
DOI: 10.1371/journal.ppat.1003278
|View full text |Cite
|
Sign up to set email alerts
|

Rab11-FIP1C and Rab14 Direct Plasma Membrane Sorting and Particle Incorporation of the HIV-1 Envelope Glycoprotein Complex

Abstract: The incorporation of the envelope glycoprotein complex (Env) onto the developing particle is a crucial step in the HIV-1 lifecycle. The long cytoplasmic tail (CT) of Env is required for the incorporation of Env onto HIV particles in T cells and macrophages. Here we identify the Rab11a-FIP1C/RCP protein as an essential cofactor for HIV-1 Env incorporation onto particles in relevant human cells. Depletion of FIP1C reduced Env incorporation in a cytoplasmic tail-dependent manner, and was rescued by replenishment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

10
133
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(144 citation statements)
references
References 60 publications
10
133
1
Order By: Relevance
“…For HIV-1, the CT is required for Env incorporation into particles in physiologically relevant cell types, such as peripheral blood mononuclear cells, monocyte-derived macrophages, and most T-cell lines (8,9). Recent work has shown that the CT mediates an interaction with Rab11 familyinteracting protein 1c (FIP1c), which in turn interacts with Rab14 and appears to direct trafficking of HIV-1 Env to sites of assembly; it is likely that interactions with FIP1c contribute to the observed requirement for the CT in Env incorporation (10,11). It is, however, unclear why lentiviral CTs are so large, because far smaller Env CTs also contain essential functional trafficking and signaling motifs (12).…”
mentioning
confidence: 99%
“…For HIV-1, the CT is required for Env incorporation into particles in physiologically relevant cell types, such as peripheral blood mononuclear cells, monocyte-derived macrophages, and most T-cell lines (8,9). Recent work has shown that the CT mediates an interaction with Rab11 familyinteracting protein 1c (FIP1c), which in turn interacts with Rab14 and appears to direct trafficking of HIV-1 Env to sites of assembly; it is likely that interactions with FIP1c contribute to the observed requirement for the CT in Env incorporation (10,11). It is, however, unclear why lentiviral CTs are so large, because far smaller Env CTs also contain essential functional trafficking and signaling motifs (12).…”
mentioning
confidence: 99%
“…In Qi et al (35), Ser-580 and Ser-582 were mutated to asparagine and leucine, respectively, to match the residues of the corresponding positions in FIP2 (Fig. 5B) (35). However, inspection of this region revealed that the amino acid in FIP2, which aligns with Ser-582 of RCP, is in fact a phenylalanine and not a leucine (Fig.…”
Section: Gel Filtration Analyses Of Rab14mentioning
confidence: 99%
“…5A) were subjected to an overlay assay with GST-Rab11A and GST-Rab14 to further clarify the Rab-binding region. In Qi et al (35), Ser-580 and Ser-582 were mutated to asparagine and leucine, respectively, to match the residues of the corresponding positions in FIP2 (Fig. 5B) (35).…”
Section: Gel Filtration Analyses Of Rab14mentioning
confidence: 99%
See 2 more Smart Citations